Becoming carbon neutral in Costa Rica to be more sustainable: an AHP approach - Valenciano-Salazar, Jorge A. (2020)
We propose addressing an organization’s adoption of an environmental certification as a multicriteria problem considering environmental sustainability as well as economic and strategic aspects. The Analytical Hierarchy Process (AHP) was empirically applied to analyze the adoption decision of several Costa Rican firms and institutions. We select a set of economic, strategic, and environmental criteria that seem relevant for the organization’s direction according to our literature review and a series of face-to-face interviews with scholars and companies’ managers. As an environmental certification, we focus on Carbon Neutral (CN), which is a domestic certification aimed at reducing or offsetting carbon emissions and ISO 14001, which is a well-known international standard aimed at compliance with environmental norms. We conduct the AHP analysis using the answers given by 24 companies and institutions, which in aggregate terms, give CN a higher score than ISO 14001 due to the fact that CN ranks above ISO 14001 when attending to environmental sustainability, although ISO 14001 tends to be preferred in economic and strategic terms.